2012
DOI: 10.1007/s10531-012-0370-7
|View full text |Cite
|
Sign up to set email alerts
|

The ecosystem functioning dimension in conservation: insights from remote sensing

Abstract: An important goal of conservation biology is the maintenance of ecosystem processes. Incorporating quantitative measurements of ecosystem functions into conservation practice is important given that it provides not only proxies for biodiversity patterns, but also new tools and criteria for management. In the satellite era, the translation of spectral information into ecosystem functional variables expands and complements the more traditional use of satellite imagery in conservation biology. Remote sensing scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
79
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 125 publications
0
79
0
7
Order By: Relevance
“…Recently, the ecosystem functioning dimension of biodiversity has gained attention [3] given that global change effects on biodiversity are particularly noticeable at the ecosystem level [4] and have a faster influence on functional than on structural or compositional characteristics of ecosystems [5,6]. Thus, understanding how environmental and human factors operate on the functional dimension of biodiversity at different scales is critical for sustaining and enhancing the Earth's ecosystems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, the ecosystem functioning dimension of biodiversity has gained attention [3] given that global change effects on biodiversity are particularly noticeable at the ecosystem level [4] and have a faster influence on functional than on structural or compositional characteristics of ecosystems [5,6]. Thus, understanding how environmental and human factors operate on the functional dimension of biodiversity at different scales is critical for sustaining and enhancing the Earth's ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Our definition of EFTs is based on estimators of the seasonal dynamics of carbon gains, but remote sensing may provide additional functional variables to complement ecosystem functioning descriptions at the same and different spatial and temporal resolutions [3,86,87]. For instance, Fernández et al [23] showed how adding shortwave albedo and surface temperature, two variables closely linked to the exchange of energy in ecosystems, to carbon gains descriptors helped to complement the ecosystem functioning characterization at more detailed spatial resolutions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In accordance with the development of remote sensing and geographic information system (GIS), more and more researchers have been engaged in adopting them to evaluate the state of ecosystem in many aspects, such as the ecological security in urban ecosystem (Masek et al 2000;Singh et al 2009;Naeimi et al 2013;Xu et al 2014) and in mining areas (Ma et al 2013), ecological vulnerability in mountainous regions (Li et al 2006;Song et al 2010), ecological health in rivers and wetlands (Luo 2006;Coskun 2009), and ecosystem function in conservation areas (Halim et al 2008;Cabello et al 2012;Lebed et al 2012).…”
Section: Introductionmentioning
confidence: 99%